2015
DOI: 10.1016/j.jelekin.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on neuromuscular function of elbow flexors and knee extensors of type 2 diabetic patients

Abstract: Massimo (2015) Effect of exercise training on neuromuscular function of elbow flexors and knee extensors of type 2 diabetic patients. Journal of Electromyography and Kinesiology, 25 (5). pp. 815-823.Downloaded from: http://insight.cumbria.ac.uk/2048/ Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 60 publications
3
16
0
Order By: Relevance
“…In a study on aerobic and resistance training, it has been shown that aerobic capacity improves by 13% and muscle strength improves by 14%–20% in healthy men of the same age as our cohort when exercise is performed twice weekly for 21 weeks . In patients with diabetic neuropathy, muscle strength increases by 11%–19%, and aerobic capacity increases by 12% . In muscle diseases, an improvement of aerobic capacity of 14% was noted in congenital myopathy along with an increase in muscle strength of 60% in limb‐girdle and Becker muscular dystrophies .…”
Section: Discussionsupporting
confidence: 51%
“…In a study on aerobic and resistance training, it has been shown that aerobic capacity improves by 13% and muscle strength improves by 14%–20% in healthy men of the same age as our cohort when exercise is performed twice weekly for 21 weeks . In patients with diabetic neuropathy, muscle strength increases by 11%–19%, and aerobic capacity increases by 12% . In muscle diseases, an improvement of aerobic capacity of 14% was noted in congenital myopathy along with an increase in muscle strength of 60% in limb‐girdle and Becker muscular dystrophies .…”
Section: Discussionsupporting
confidence: 51%
“…Few studies have examined the mechanisms of fatigability among people with diabetes. Several studies have shown that for isometric contractions with lower-limb muscles (ankle dorsiflexor and knee extensor muscles), people with type 1 diabetes and diabetic polyneuropathy and people with T2D were more fatigable than controls (3,6,8). The mechanisms contributing to greater fatigability in the people with type 1 diabetes who had diabetic polyneuropathy included disruption of neuromuscular transmission indicated by a concomitant decrease in the maximal compound muscle action potential (3) and slowed motor unit conduction velocities and discharge frequencies (6).…”
Section: Introductionmentioning
confidence: 99%
“…There are no other known studies determining the fatigability during dynamic fatiguing tasks in people with T2D, and, furthermore, the mechanisms are unknown. Finally, despite potential differences in fatigability between men and women (25), studies of fatigability in people with T2D have been underpowered to determine whether there are sex-related differences among people with T2D (e.g., 8,18,28,37).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, elderly individuals exhibit lower MU discharge rates . However, the cause–effect relation in these age‐related adaptations is unknown, mainly because of the lack of methods that allow direct access to motor neurone behaviour and muscle unit properties concurrently, in large samples of MUs in vivo .…”
mentioning
confidence: 99%